THE STUDY OF THE EFFECT OF ANNEALING ON OPTICAL PROPERTIES TO CUALS2 THIN FILMS - SATTAR S. IBRAHIM; UTHMAN S. IBRAHIM; JASSIM M. SALEH (مجلة جامعة الانبار للعلوم الصرفة, 2009)
In this research the study of optical properties for thin films of (CuAlS2) Compound , has been Carried out in sintered temperature (360)C0 . using heat spray method. The effect of substituted Sodium element and annealing at temperatures (250 , 300 , 350 , 400) C0 for two hours has bean studied, the effect of heat neutrons irradiation at doses (3.024*10 9, 4.752*109 , 6.48*109)n.cm-2 has also been shown.Optical constant have also been measured by the absorption and permeability spectrum in wavelength rang (300- 1000)nm .such a procedure will eables finding many parameters, such as Coefficient of optical absorption , which found to be grater then (105) for all films , allowed of electrons transation , Limit of absorbiption will be shift to highest long wave depending on substituted ,annealing or irradiation limt of optical absorpition found to full is the range between (540-590)nm . The value of energy gap for (CuAlS2) thin films found to be (3.2)eV . This value has been increased with annealing and irradiation by neutrons and become (3.25.2.3,3.4,3.5) eV, respectively according to the above values of energy gaps (3.28,3.4,3.48) eV substituted Sodium element in (CuAlS2) at (1-5)wt%. This causes reduction in energy gap, and that reduction was (3.2) eV for unsubstituted compound and (2.85) eV for substituted with (5)wt% ratio